(untitled) (Global Journal of Science Frontier Research, 2024)
In this paper we calculated the self-interaction of the gravitational field, and analyzed the effect of the self-interactions in a general static isotropic gravitational field using a semi classical approach. We found that the effects of the self -interaction in the gravitational field can be used to explain dark matter.